Solar energy for societal decarbonisation: a perspective on emerging opportunities in utility-scale solar electricity and solar in the built environment - Meredith, Paul (Frontiers in Sustainable Cities, 2024)
The solar resource presents almost limitless opportunities for creating clean energy – not just in the form of solar-derived electricity, but also to drive heating and cooling cycles, create solar fuels, or indeed to promote chemical and biochemical pathways for the production of food, clean water and raw materials. There is an ever-expanding plethora of applications for solar energy as a critical contributor to global decarbonization. This short Perspective is focused on two of the largest opportunities for solar energy to make major emissions reduction and deliver societal fairness and economic impacts: notably utility-scale electricity generation and the more local opportunities of the built environment. We examine the two dominant forms of solar energy – the direct generation of electrical power via the photovoltaic effect, and the indirect generation of electricity (and indeed heating and cooling energy) through solar thermal cycles. As a Perspective, it provides necessary background for the general reader, but also seeks to emphasise the specific challenges and opportunities for the interested specialist.